Stories of resilience—public housing communities and the Kuala Lumpur community gardens initiative - Mohd Sharif, Shahida; Ujang, Norsidah; Abdul Shukor, Shureen Faris; Maruthaveeran, Sreetheran (Springer Nature, 2024)
The COVID-19 pandemic saw cities worldwide implementing various pandemic mitigation measures, including social and physical distancing, among others. However, these measures did not deter numerous public housing residents from continuing their participation in community gardening initiatives. This seemingly atypical behaviour sparked an interest in investigating these individuals’ social characteristics and commitment to community gardening initiatives through semi-structured interviews. Recruitment of participants was done through a series of multi-stage sampling: purposive, followed by a snowball. The findings revealed that many of the participants were retirees and homemakers, with a balanced gender composition. They were primarily seniors between the ages of 60 and 75, with only a few from the 40–50 age range. Their time commitments in the community gardens revealed vast differences between genders, with the men devoting more of their day to community gardening than the women, and the interviews revealed why. The combined documentation of the characteristics and stories of the participants could provide researchers, policymakers, and local authorities with critical information about the community’s needs, strengths and experiences, driving planning, policy development and decision-making to be in sync with the norms and perspectives of the public housing residents of Kuala Lumpur.